Analysis of the Role of Online Matchmaking Agency in Finding a Partner in Palembang City - Muhammad Nurhadi Mulia; Khoiril Sabili; Wulan Sari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Penomena the emergence of many online matchmaking agency sites that are used by the public to find a life partner due to technological advances and busyness at work is one of the causes of the rampant use of online matchmaking agency services today inseparable from the development of the times facing the industrial revolution 4.0 which focuses on the role and benefits of the needs or guidance of online matchmaking sites. This study uses qualitative proximity with the intention of describing descriptively what will be studied, and primary data sources in the form of interviews with 6 sources and for secondary data in the form of articles from previous authors that discuss online matchmaking bureaus in detail and detail. The results of this study explain that online matchmaking agencies are currently not very useful, especially when looking for a soul mate, it is not feasible in his opinion to search through online matchmaking agencies, because marriage is not a common thing that can be called a sacred thing because marriage is not only a meeting of men and women but to unite both families as well, therefore you have to be more selective in finding a partner.